2020
DOI: 10.1021/acs.jpclett.0c00443
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Origin of Phase-Transformation Kinetics of CsPbI3 Perovskite Nanocrystals Based on Activation Energy Measurements

Abstract: Perovskite α-CsPbI3 nanocrystals (NCs) with a high fluorescence quantum yield (QY) typically undergo a rapid phase transformation to a low-QY δ-CsPbI3 phase, thus limiting their optoelectronic applications. In this study, organic molecule hexa­methyl­di­sila­thiane (HMS) is used as a unique surfactant to greatly enhance the stability of the cubic phase of CsPbI3 NCs (HMS-CsPbI3) under ambient conditions. The reaction kinetics of the phase transformation of CsPbI3 NCs are systemically investigated through in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
1
21
0
1
Order By: Relevance
“…We attribute the highest PLQY of 96% for 135@NCs to their longest excited state lifetime, as will be detailed in following section. Note that this (96%) is one of the highest PLQY among all the reported values for pristine CsPbI 3 NCs (which are typically below 90% [28][29][30] ). All the samples exhibit narrow emission bands, indicating that the size distribution of as-formed NCs can be precisely controlled.…”
Section: Optical Properties Of As-synthesized Cspbi 3 Ncsmentioning
confidence: 76%
“…We attribute the highest PLQY of 96% for 135@NCs to their longest excited state lifetime, as will be detailed in following section. Note that this (96%) is one of the highest PLQY among all the reported values for pristine CsPbI 3 NCs (which are typically below 90% [28][29][30] ). All the samples exhibit narrow emission bands, indicating that the size distribution of as-formed NCs can be precisely controlled.…”
Section: Optical Properties Of As-synthesized Cspbi 3 Ncsmentioning
confidence: 76%
“…Usually, long-chain ligands such as oleylamine (OLA) and oleic acid (OA) are easily detached from the surface of NCs during the purification process, which leads to poor stability. It is reported that optical properties and stability of CsPbI 3 NCs in harsh environments can be improved by using short-chain ligands or ligands with multiple functional groups, such as hexamethyldisilathiane (HMS), sodium dodecyl sulfate (SDS), didodecyldimethylammonium bromide (DDAB), 2,2′-iminodibenzoic acid (IDA), etc. However, the dynamic bonding process between the ligand and NC surface is not very clear, and the preparation process of ligand exchange is complex, which requires appropriate synthesis conditions and then brings difficulties to the preparation of efficient and stable CsPbI 3 NCs …”
mentioning
confidence: 99%
“…To further understand the influence of laser illumination, systematic power-and wavelengthdependent studies are performed on the LAPT process. Given that moisture is known to accelerate the high-T to low-T phase transformation, 5,13,14,21 we first investigate LAPT under different moisture levels (Figure 3D). We find that moisture and laser exhibit a coupling effect.…”
Section: Resultsmentioning
confidence: 99%